Стационарное движение квантовой частицы в поле одномерного потенциала произвольного вида - А. Ж. Хачатрян; Д. М. Седракян; В. А. Хоецян (ՀՀ ԳԱԱ հրատ.)
В работе развит последовательный подход для задачи описания стационарного движения квантовой частицы в поле одномерного потенциала произвольного вида. Աշխատանքում զարգացված է հետևողական մոտեցում` կամայական տեսքի միաչափ պոտենցիալի դաշտում քվանտային մասնիկի ստացիոնար շարժման նկարագրման համար: A new approach to the problem of description of the stationary motion of a quantum particle is developed. It is shown that the wave function of infinite motion with the accuracy to arbitrary constants can be presented using an arbitrary single solution for a some set of linear differential equations of the first order.
Keywords: Physics; Science; Nuclear Physics